Experimental and numerical study of a compact inline swirler for gas–liquid separation. (16th January 2023) - Maluta, Francesco; Paglianti, Alessandro; Montante, Giuseppina
Highlights: CFD and experiments characterized a compact inline swirler for air–water separation. Liquid velocity, pressure drop, and gas distribution were experimentally measured. Experimental validation of RANS-TFM results obtained with three turbulence models. Bubble Size Distribution predicted with a PBE agrees with experimental measurements. The proposed and validated modelling approach can be used to design inline swirlers. Abstract: The liquid mean and fluctuating velocity field, the pressure drop, the gas-phase distribution and the bubble size distribution in a compact inline swirler for gas–liquid separation were experimentally measured. The results served as validation for the proposed computational approach and the most suitable turbulence model was identified. The gas phase distributions obtained considering both a constant bubble diameter and the local bubble size distribution (BSD) through the solution of a Population Balance Equation (PBE) confirmed the lighter gas phase accumulation towards the pipe centre. The study highlights that to realistically predict the BSD a coupled solution of the PBE with the flow equations is needed and that the resulting distribution is relatively narrow. The gas accumulation zone obtained coupling the solution of the PBE is in good agreement with the experimental one. It is shown that CFD may help the design of inline swirlers for gas–liquid separation.